2001
DOI: 10.1002/1521-3773(20010716)40:14<2651::aid-anie2651>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

First O−H−N Hydrogen Bond with a Centered Proton Obtained by Thermally Induced Proton Migration

Abstract: Within a range of 0.1 Å, the H atom in the O−H−N hydrogen bond of the adduct 4‐methylpyridine⋅pentachlorophenol could be shifted by a simple adjustment of temperature (see scheme). At approximately 90 K the H atom is exactly centered between the O and the N atoms, as could be shown by stepwise monitoring by using variable‐temperature single‐crystal neutron diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
239
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(249 citation statements)
references
References 28 publications
9
239
0
1
Order By: Relevance
“…Incoherent tunneling, via excited vibrational states, dominates the rate of PT at all temperatures since the potential barrier, estimated to be 2000 K [23], is always significantly greater than kT. However, in short HBs, the direct observation of tunneling processes has, to our knowledge, never been reported despite many experimental [24][25][26][27][28] and theoretical [29][30][31][32][33][34][35][36] studies. is an almost perfect model system in which to study PT in a very short HB (Fig.…”
mentioning
confidence: 99%
“…Incoherent tunneling, via excited vibrational states, dominates the rate of PT at all temperatures since the potential barrier, estimated to be 2000 K [23], is always significantly greater than kT. However, in short HBs, the direct observation of tunneling processes has, to our knowledge, never been reported despite many experimental [24][25][26][27][28] and theoretical [29][30][31][32][33][34][35][36] studies. is an almost perfect model system in which to study PT in a very short HB (Fig.…”
mentioning
confidence: 99%
“…In fact, it has been shown recently that this is the case. Steiner et al have monitored the temperature dependent migration of protons in weak hydrogen bonds with neutron diffraction [13]. Furthermore, the expectation that weak dative bonds may also be promising candidates gains further support from the work of Lewiński et al, who have nicely demonstrated that hydrogen bonds and dative bonds have similar energies in the class of compounds considered in this work [14].…”
Section: Introductionmentioning
confidence: 76%
“…As shown in Figure 1a, the asymmetric unit of 1-Cl comprises one Fe(II) complex and one H2Cl2TPA molecule. The molecular arrangement shows that a zig-zag chain was formed with an alternating arrangement of Fe(II) complexes and H2Cl2TPA molecules via hydrogen bonds formed between the N atom in the terminal Py ring in the Fe(II) complex and a carboxyl group in H2Cl2TPA (Figure 1b [13][14][15]. Regarding the temperature dependency of hydrogen bond distances, studies have reported that the hydrogen bond distance …”
Section: Methodsmentioning
confidence: 99%
“…The molecular arrangement shows that a zig-zag chain was formed with an alternating arrangement of Fe(II) complexes and H 2 Cl 2 TPA molecules via hydrogen bonds formed between the N atom in the terminal Py ring in the Fe(II) complex and a carboxyl group in H 2 Cl 2 TPA (Figure 1b). The N4···O3 hydrogen bond distance in the terminal pyridine ring was relatively long (N4···O3 = 2.663 Å), whereas the N8···O5 hydrogen bond distance was relatively short (N8···O5 = 2.552 Å) at 123 K. The N4···O3 and N8···O5 hydrogen bond distances in 1-Br were slightly longer (N4···O3 = 2.681 Å, N8···O5 = 2.560 Å) than those in 1-Cl at 123 K. The N8···O5 bond distances in 1-Cl and 1-Br were short for a N···O-type hydrogen bond but slightly longer than those commonly observed in organic compounds that exhibit proton migration induced by temperature change [13][14][15]. Regarding the temperature dependency of hydrogen bond distances, studies have reported that the hydrogen bond distance between the Py ring in isonicotinic acid hydrazide, a precursor of L, and the carboxyl group tends to increase with increasing temperature [16][17][18].…”
Section: Methodsmentioning
confidence: 99%